Efikasi Diri Menyusui Ibu Bekerja Berperan Penting Dalam Pemberian Asi Eksklusif - Dewi Irianti; Iis Pusparina; Filia Sofiani Ikasari (Journals of Ners Community, 2023)
Breastfeeding self-efficacy is a predictor of the duration of exclusive breastfeeding. Working mothers can influence the decision of mothers who give birth to exclusively breastfeed. The purpose of this study was to determine the relationship between breastfeeding self-efficacy of working mothers and exclusive breastfeeding. The study design was cross-sectional. One hundred working mothers in the Martapura I Health Center Work Area became the research sample, taken by consecutive sampling. Analysis using Chi Square test. There is a significant relationship between breastfeeding self-efficacy of working mothers and exclusive breastfeeding. Self-efficacy of breastfeeding working mothers needs to be improved so that exclusive breastfeeding also increases